Global publication trends and research trends of necroptosis application in tumor: A bibliometric analysis - Wu, Yun-Yun; Li, Chang-chun; Lin, Xiao; Xu, Feng; Shan, Su-Kang; Guo, Bei; Li, Fu-Xing-Zi; Zheng, Ming-Hui; Xu, Qiu-Shuang; Lei, Li-Min; Duan, Jia-Yue; Tang, Ke-Xin; et al. (Frontiers in Pharmacology, 2023)
Background: necroptosis is an alternative, caspase-independent programmed cell death that appears when apoptosis is inhibited. A growing number of studies have reflected the link between necroptosis and tumors. However, only some systematical bibliometric analyses were focused on this field. In this study, we aimed to identify and visualize the cooperation between countries, institutions, authors, and journals through a bibliometric analysis to help understand the hotspot trends and emerging topics regarding necroptosis and cancer research. Methods: The articles and reviews on necroptosis and cancer were obtained from the Web of Science Core Collection on September 16, 2022. Countries, institutions, authors, references, and keywords in this field were visually analyzed by CtieSpace 5.8.R3, VOSviewer 1.6.18, and R package “bibliometrix.” Results: From 2006 to 2022, 2216 qualified original articles and reviews on necroptosis in tumors were published in 685 academic journals by 13009 authors in 789 institutions from 75 countries/regions. Publications focusing on necroptosis and cancer have increased violently in the past 16 years, while the citation number peaked around 2008-2011. Most publications were from China, while the United States maintained the dominant position as a “knowledge bridge” in necroptosis and cancer research; meanwhile, Ghent University and the Chinese Academy of Sciences were the most productive institutions. Moreover, only a tiny portion of the articles were multiple-country publications. Peter Vandenabeele had the most significant publications, while Alexei Degterev was most often co-cited. Peter Vandenabeele also gets the highest h-index and g-index in this research field. Cell Death & Disease was the journal with the most publications on necroptosis and cancer, which was confirmed to be the top core source by Bradford’s Law. At the same time, Cell was the leading co-cited journal, and the focus area of these papers was molecular, biology, and immunology. High-frequency keywords mainly contained those that are molecularly related (MLKL, NF-kB, TNF, RIPK3, RIPK1), pathological process related (necroptosis, apoptosis, cell-death, necrosis, autophagy), and mechanism related (activation, expression, mechanisms, and inhibition). Conclusion: This study comprehensively overviews necroptosis and cancer research using bibliometric and visual methods. Research related to necroptosis and cancer is flourishing. .